Prevalence of cryptosporidiosis in HIV-infected patients in Kajang Hospital, Selangor - Lim, Yvonne Ai Lian; Mahmud, Rohela; Sim, B.L.; Ibrahim, Jamaiah; M., Nurbayah (SEAMEO Regional Tropical Medicine and Public Health Network, 2005)
A total of 66 fecal specimens obtained from patients infected with human immunodeficiency virus (HIV) from Kajang Hospital were screened for Cryptosporidium oocysts. The fecal specimens were concentrated using the formalin ethyl acetate concentration technique, stained with modified Ziehl-Neelsen and confirmed with immunofluorescence stain. It was established that 2 (3.0) were positive for Cryptosporidium. The two cases involved a Chinese local man (with diarrhea) and an Indonesian foreigner (without diarrhea). A higher index of suspicion for clinical cryptosporidiosis in HIV patients, including those with chronic weight loss with or without diarrhea, is recommended. In addition, laboratory testing for Cryptosporidium in HIV-infected patients is highly recommended in order to have a better understanding of the epidemiology and management of the disease in Malaysia.